2020
DOI: 10.3390/nu12061590
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Adequacy of Commercial Complementary Cereals in Germany

Abstract: Commercial cereals are among the first complementary foods fed to infants in Germany and elsewhere. The purpose of this national survey is to describe the nutritional adequacy of commercial complementary cereals. A comprehensive, cross-sectional survey of cereal manufacturer websites (n = 15) was conducted from March to April 2019. Food labels were analyzed for iron, zinc, iodine, sodium, and sugar contents in commercial complementary cereals, and ingredient lists were evaluated for whole grains and added suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The maximum level is regulated; for example, in Europe the iodine content of complementary foods should not exceed 35 µg/100 kcal ( 213 ). However, recent data from Germany suggest commercial complementary cereals are rarely fortified with iodine and are generally poor sources of iodine ( 214 ).…”
Section: Dietary Sources Of Iodinementioning
confidence: 99%
“…The maximum level is regulated; for example, in Europe the iodine content of complementary foods should not exceed 35 µg/100 kcal ( 213 ). However, recent data from Germany suggest commercial complementary cereals are rarely fortified with iodine and are generally poor sources of iodine ( 214 ).…”
Section: Dietary Sources Of Iodinementioning
confidence: 99%
“…Although cereals are usually considered readily available healthy breakfast items, many of these commercially available processed cereals are a source of high sugar [ 24 ]. A research team in Germany found that almost one-third of the commercially available cereals contain added sugars [ 25 ]. Therefore, consumers must check the ingredients and choose the cereals which are more wholesome and contain fiber and dried fruits [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, more than half of the evaluated products contained added sugars in different forms (sucrose, brown sugar, glucose, and honey), and the average sugar content was 23.2 g/100 g, being around 24% of the total calories of infant cereals. The sucrose was the most used sweetener, similar to those found in German infant cereals [ 19 ]. Maalouf et al [ 21 ] evaluated the sugar content stated on the label of the USA commercial instant infant cereals (dry) and found an average value of 12 g/100 g, and 12% of products have one source of added sugars.…”
Section: Discussionmentioning
confidence: 58%
“…Wheat and rice flours are the main cereals used in infant cereals, depending on whether porridges contain gluten (72.5%) or are gluten-free (27.5%). Four out of 12 brands included some products with whole-grain flours; complementary cereals marketed in Germany have shown that half of the products are formulated with whole-grain flours [ 19 ]. Most brands state in labels that cereals suffer a hydrolysis process; however, label information does not clarify whether companies hydrolyze the cereals in the manufacturing process or if they purchase hydrolyzed cereals.…”
Section: Discussionmentioning
confidence: 99%